ANALISIS PERMINTAAN KAYU LAPIS DI JAWA - Satria Astana; Buharman Buharman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
One of the main important things for the planning of production and marketing development is the demand informations. This research was conducted to analyse the aggregate demand of plywood in the districts of Java and its determining factors. The result of this research revealed that the aggregate demand of plywood in the districts of Java ranged from 679. 731 m3 to 1741.841 m3. The number of people and the gross domestic regional income in the districts determine the aggregate demand of plywood significantly. The elasticity of the number of people is 0.12 and the gross domestic regional income is 0.16. In addition, this research found that the distribution of its consumption consisted of 60. 02% of the households, 25.22% of the building contractors, 10.97% of the furniture craft industries and 3. 79% of the car body craft industries.